Cutaneous Squamous Cell Carcinoma of the Head and Neck. (21st December 2010) - Gurudutt, Vivek V.; Genden, Eric M.
Abstract : Cutaneous squamous cell carcinoma of the head and neck is an epidemic that reaches all parts of the world. Making the diagnosis relies on the acumen of the clinician and pathologist. Various pathologic subtypes exist and differ in histology and prognosis. High-risk tumors need aggressive treatment and vigilant surveillance to monitor for recurrence. Large tumors, deep tissue invasion, perineural involvement, recurrence, location in high-risk areas, and immunosuppression are implicated in worsening prognosis. Surgery is the mainstay of treatment with adjuvant radiation therapy as needed for aggressive tumors; however, other modalities are potentially useful for low-risk lesions. The use of Mohs surgery has become increasingly useful and has shown high success rates. Involvement of parotid and neck lymph nodes significantly affects outcomes and the physician should be comfortable with management of this complex disease. This paper examines the diagnosis, pathology, clinical course, and treatment options for cutaneous squamous cell carcinoma of the head and neck.